(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
In modern conditions of development of the higher education system, requirements are put forward for graduates related not only to knowledge, skills and abilities in the professional field. Personal qualities such as independence, initiative, originality of thinking, communication skills, the ability to generate ideas, readiness to solve problem situations that do not have predeveloped algorithms and means of solution, are not less important. They all have great importance in the further educational and professional activities of an architect, designer, engineer. In the overall task of improving the educational process, perhaps the most important problem is the quality of teaching, which largely depends on the teaching methodology. Drawing is the international language of architectural and artistic specialists and engineers of various specialties. The disciplines of the graphic cycle, which include descriptive geometry and engineering graphics, are studied by students of architectural, artistic and technical fields in universities in their junior years. The result of the training is the development of spatial representation, the acquisition by students of high-quality graphic skills, the ability to graphically solve applied problems, correctly create and “read” drawings, and also know the basic requirements and rules for the preparation of design documentation. The main goal of our research is to monitor and test the criteria for the effectiveness of teaching graphic disciplines during the academic year, as well as to summarize the results on the development and improvement of approaches to the methodology of teaching graphic disciplines and their impact on the quality of education of firstand second-year students in architectural, artistic and technical specialties. The work uses theoretical and empirical methods: analysis, classification and generalization of the research source base; author’s experience in organizing the educational process; diagnostics of students’ classroom graphic work with timing of time spent, as well as their homework. Our many years of experience show that junior students can gain in-depth knowledge only if they are highly motivated, systematic individual work and obtain detailed knowledge on their own. The presented results of a study of monitoring the educational process of teaching graphic disciplines and the influence on the quality of teaching of various methodological and many other important factors, from our point of view, can be assessed as quite significant, so it is necessary to continue searching in this direction in the future.